THE EFFECT OF GREEN TEA AND STEVIA EXTRACT ON LIVER HISTOPATHOLOGY WISTAR RATs TYPE II DIABETES MELLITUS - Novit, Elmawati; Sadhana, Udadi; Mahati, Endang (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Introduction: Glucose metabolism abnormality on type 2 diabetes mellitus (T2DM) caused liver damage due to dyslipidemia and increasing oxidative stress. Antidiabetic and antioxidants within green tea leaf and stevia leaf extract prevent liver damage due to T2DM complications. Objective: To investigate green tea and stevia leaf extract effects on liver histopathology on T2DM rats.Methods: This study used Post Test Only Control Group Design. A total of 30 Wistar rats were divided into 5 groups: control group (C-G), normal rats; negative control group (NC-G), T2DM induction; positive control group (PC-G), treated by Metformin; the first treatment group (T1-G), was treated by green tea leaf extract and stevia leaf extract; and the second treatment group (T2-G) was treated by a Metformin also green tea and stevia leaf extract. The treatment was given to subjects for 21 days starting 3 days after the induction of Nicotinamide (NA) and Streptozotocine (STZ). Histopathological assessment of liver cells uses assessment parameters in the form of features of necrosis, vacuolization, sinusoidal dilation and number of inflammatory cells. Hypothesis will be tested by Kruskal-Wallis (p<0,05) dan Mann-Whitney test (P<0,05) Results: The difference of liver damage in all group shows a significant difference, p<0.05. Significant differences in liver damage scores between the 2 groups there are between the negative control group and the control group (0.031), positive control (0.042), and second treatment group (0.011), and between first treatment group and second treatment group (0.041).Conclusion: The administration of green tea extract, stevia leaf, and standard drug may reduce liver damage score of Wistar with T2DM